Role of Social Protection and Disaster Management: A Bibliometric and Systematic Literature Review - Prihantika, Ita; Rahmadhani, Tia Panca; Mulyana, Nana; Sulistiowati, Rahayu; Hutagalung, Simon Sumanjoyo (Journal of Research in Social Science and Humanities, 2023)
The role of social protection has emerged as a strategy to minimize post-disaster impact by building resilience in the community. This approach is increasingly being used in post-disaster risk reduction. This study aims to review the role of disaster management and social protection in various literature through bibliometric analysis and systematic literature review using the SPAR-4-SLR protocol. The Scopus database was used to retrieve the article using selected keywords. Citations, keywords, and country analyses were used for a bibliometric review. The SPAR-4-SLR protocol was used to identify on social protection and disaster management. This study was generated over 30 years from Scopus and Google Scholar databases; over 1089 texts from various disciplines were retrieved. The bibliometric analyses revealed five different clusters were formed. Social protection and disaster management are emphasized to strengthen community resilience, especially in developing countries.